Biodiversity of Tintinnids (Tintinnida) in Khanh Hoa - Binh Thuan waters - Kieu, Nguyen Thi; Luom, Phan Tan; Vinh, Nguyen Tam; Lam, Nguyen Ngoc; P. Montoya, Joseph; Hai, Doan Nhu (Academia Journal of Biology, 2018)
Tintinnidsarean important protozoan group in the aquatic food web and had been widely studied in various waters. There are about 1000 known species in the world. However, there have beenvery few taxonomic studies in Vietnam and therefore the number of Tintinnid taxa and their distribution are poorly known. Thepresent study documents 65 tintinnids species belonging to 30 genera and 13 families in samples collected from Khanh Hoa - Binh Thuan waters in 2016 and 2017. There were 17 new taxa records for Vietnam protozoan fauna, raising the number of tintinnids recorded in Vietnam to 125 taxa. Tintinnid assemblages in Khanh Hoa-Binh Thuan waters shared about 17 species with Ha Long Bay, 32 species with Con Co island and 26 species with coastal waters of South Vietnam. Analysis of species diversity shows that the Shannon diversity index H’ varied from 1.5 to 2.6. Distribution of species numbers and diversity in the Khanh Hoa - Binh Thuan waters revealed possible combined effects of hydrographical activities (e.g. upwelling), Mekong river influent (e.g. salinity), and food available on tintinnid communities. Citation: Nguyen Thi Kieu, Phan Tan Luom, Nguyen Tam Vinh, Nguyen Ngoc Lam, Josepth P. Montoya, Doan Nhu Hai, 2017. Biodiversity of Tintinnids (Tintinnida) in Khanh Hoa - Binh Thuan waters. Tap chi Sinh hoc, 39(4): 421-433. DOI: 10.15625/0866-7160/v39n4.11033. *Corresponding author:haidoan-ion@planktonviet.org.vn Received 19 September 2017, accepted 12 December 2017